A two-stage thermal upgrading process for nickeliferous limonitic laterite ores. (October 2015) - Elliott, R.; Rodrigues, F.; Pickles, C. A.; Peacey, J.
Abstract : Sulphide ore deposits are becoming increasingly less viable as a source of nickel, driving recent interest in the development of nickel laterite deposits. The difficulties with the current methods of nickel metal production from these oxide ores arise mainly from the inability to produce a concentrate analogous to that obtained in the flotation of sulphide ores, resulting in high production costs. In this work, a two-stage reduction and thermal growth process is proposed for the treatment of the nickeliferous limonitic laterite ores to produce a ferronickel product, recoverable by magnetic separation. An initial reduction roast of the ore with 6% coal and 4% sulphur additions at 600°C for 1 h, followed by particle growth for 1 h at 1000°C, produced a ferronickel concentrate with a nickel grade of 4% and a nickel recovery of 93·2%. The impact of particle growth temperature and retention time at temperature on the ferronickel particle size was also studied. For the control conditions, typical ferronickel particles produced were 10–20 μm in size. The particle size did not significantly change at temperatures higher than 1200°C or for retention times beyond 60 min. Abstract : Les dépôts de minerai sulfuré sont de moins en moins viables comme source de nickel, poussant l'intérêt récent du développement des dépôts de latérite de nickel. Les difficultés des méthodes courantes de production du métal nickel à partir de ces minerais d'oxyde viennent principalement de l'inhabileté à produire un concentré analogue au concentré obtenu par flottation des minerais sulfurés, ayant pour résultat des coûts élevés de production. Dans ce travail, on propose un processus à deux étapes de réduction et de croissance thermiques pour le traitement de minerais de latérite limonitique nickélifère afin d'obtenir un produit de ferronickel, récupérable par séparation magnétique. Un grillage réducteur initial du minerai, avec additions de 6% de charbon et 4% de soufre, à 600°C pendant une heure, suivi par la croissance de particule pendant une heure à 1000°C, a produit un concentré de ferronickel avec une qualité de nickel de 4% et une récupération de 93·2% du nickel. On a également étudié l'impact de la température de la croissance de particule et de la durée de rétention à la température sur la taille de particule du ferronickel. Sous ces conditions de contrôle, les particules typiques de ferronickel produites avaient une taille de 10 à 20 μm. La taille de particule n'a pas changé de façon significative à des températures plus élevées que 1200°C ou pour des durées de rétention au-delà de 60 min.